The Influence Of Price, Brand, Product Quality On The Purchase Of Thrifting Goods - Sari, Jione Oktabriana (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: The purpose of this study is to examine how price, brand, and product quality affect consumers' decisions to buy used items and to comprehend how these three elements interact to affect customer choices. Design/Method/Approach: This research uses a quantitative approach with a simple regression analysis design. Using the purposive sampling approach, 40 thrift store shoppers made up the research sample. This information was derived from a survey that measured brand, price, product quality, and purchase decisions using a Likert scale. Research Finding: The findings indicate that the decision to buy used products is significantly influenced by price, brand, and product quality. Lower prices are the main attraction for consumers, while brands that are known to provide a sense of security and good product quality also play an important role in purchasing decisions. Theoretical contribution/Originality: This research contributes to the development of consumer behavior literature, especially in the context of the thrifting market. This research also fills a limited research gap on the interaction between price, brand, and product quality in influencing second-hand purchase decisions, which has not been widely studied before. Practitionel/Policy implication: For thrifting businesses, the results of this study provide insight into designing more effective marketing strategies, such as emphasizing product quality, brand image, and offering competitive prices. In addition, this research can also be used as a reference in designing marketing policies that are in accordance with consumer preferences. Research limitation: This study has a limitation on the sample size, only 40 respondents from one region, which may not fully represent the wider population. In addition, this study only examines the three main factors that influence purchasing decisions without considering other psychological or social factors.